Neonatal Feeding Tube Colonization and the Potential Effect on Infant Health: A Review - Parker, Leslie A.; Magalhães, Marina; Desorcy-Scherer, Katelyn; Torrez Lamberti, Monica; Lorca, Graciela L.; Neu, Josef (Frontiers in Nutrition, 2022)
Background: Infants in the neonatal intensive care unit (NICU) often require feeding tubes (FT) for weeks to months. Because FTs are in near constant contact with human milk and/or formula, rapid and extensive bacterial growth is possible. Due to their immature immunologic and gastrointestinal systems, infants may be at significant health risk due to FT colonization. In adults, length of time FTs remain in place (dwell time) affects the degree of colonization and biofilm formation which is important in infants whose tubes remain in place up to 30 days. Objective: The purpose of this review was to describe and summarize the evidence regarding FT bacterial colonization in infants and identify gaps needing further investigation. Methods: Medline, CINAHL, and Embase databases were searched for clinical and/or laboratory-based observational and randomized controlled studies investigating the presence of bacteria in neonatal FTs. Results: This review of ten studies found evidence that neonatal FTs may contain high quantities of potentially pathogenic and antibiotic resistant bacteria and longer dwell times may increase the bacterial load. Furthermore, evidence suggests FT colonization may be nosocomial in origin and contribute to adverse infant health. Feeding tubes are an unrecognized source of bacterial colonization which may increase morbidity in premature infants and thus the presence of bacteria in FTs is an important area of investigation in the nutritional care of vulnerable infants in the NICU. Implications: Further appropriately powered studies which are clinically based, use appropriate analyses, and control for potential covariates is necessary to make clinical recommendations.